2022
DOI: 10.1007/s12144-022-03089-9
|View full text |Cite
|
Sign up to set email alerts
|

Should I buy or not? Revisiting the concept and measurement of panic buying

Abstract: Following various precautionary measures as executed by the government to curb the transmission of COVID-19, erratic changes in the form of temporary lockdowns and movement restrictions have created an emergency phenomenon—panic buying. While such consequence has emerged as a timely and relevant topic, reviewed literature indicate an apparent oversight for portraying panic buying through the perspectives of impulsive and compulsive consumptions. Given the gap in the association between panic buying and consume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 147 publications
(204 reference statements)
0
11
0
Order By: Relevance
“…TPB model is criticized for not consider external factors that affect consumers' purchasing behavior; therefore, social media exposure is added to replenish TPB. In addition, more and more scholars have confirmed the positive correlation between social media interaction and brand trust and product attitude (Cham et al, 2022a;Hajli, 2014). The findings from the studies by Hern andez-M endez et al (2015) and Cham et al (2022b) also revealed that electronic word-of-mouth and convenient social media information collection had a favorable effect on travelers' attitudes and their behavioral intentions.…”
Section: Social Media Exposurementioning
confidence: 92%
“…TPB model is criticized for not consider external factors that affect consumers' purchasing behavior; therefore, social media exposure is added to replenish TPB. In addition, more and more scholars have confirmed the positive correlation between social media interaction and brand trust and product attitude (Cham et al, 2022a;Hajli, 2014). The findings from the studies by Hern andez-M endez et al (2015) and Cham et al (2022b) also revealed that electronic word-of-mouth and convenient social media information collection had a favorable effect on travelers' attitudes and their behavioral intentions.…”
Section: Social Media Exposurementioning
confidence: 92%
“…, 2022). The presence of flexibility is indispensable for manufacturing firms aiming to bolster the resilience of their supply chains, particularly in the face of a dynamic business environment (Cham et al. , 2022; Piprani et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Flexibility enacts a crucial role in addressing uncertainties in the volatile business ecosystem (Cheng et al, 2022). The presence of flexibility is indispensable for manufacturing firms aiming to bolster the resilience of their supply chains, particularly in the face of a dynamic business environment (Cham et al, 2022;Piprani et al, 2022). A manufacturing firm's flexibility denotes the firm's capability in altering its production processes, logistics, and new product introduction/development, quickly and effectively in order to react to changes in the business ecosystem, particularly changes in end-consumer demand (Sreedevi and Saranga, 2017).…”
Section: Supply Chain Flexibilitymentioning
confidence: 99%
“…Some researchers had revealed that trust in AI is essential in adopting AI systems to build user intention to use AI-powered smart home devices, for it is a key aspect of the acceptability of new technologies. The slow adoption rate may be due to the lack of trust among users, as trust plays a crucial role in building relationships among human beings (Cham et al , 2022a; Cham et al , 2022b; Prufer et al , 2014; Ziefle et al , 2013). Undoubtedly, potential users may have a high level of concern about data breaches and system failures when it comes to smart home technology, especially AI-powered smart home devices.…”
Section: Literature Reviewmentioning
confidence: 99%